Review on design and development of cryogenic machining setups for heat resistant alloys and composites. (August 2021) - Khanna, Navneet; Agrawal, Chetan; Pimenov, Danil Yu; Singla, Anil Kumar; Machado, Alisson Rocha; da Silva, Leonardo Rosa Ribeiro; Gupta, Munish Kumar; Sarikaya, Murat; Krolczyk, Grzegorz M.
Abstract: Cryogenic machining is becoming a sustainable choice due to its extraordinary performance (such as non-toxic and environmentally friendly) superiority to other traditional coolants and lubricants to produce products with superior quality. This paper also critically reviews improvements in designing the cryogenic delivery setup used by researchers for machining low machinability materials like titanium alloys, nickel alloys, ferrous alloys, composites, and other difficult-to-cut materials. It also briefs the economic and sustainable perspective of this state-of-art technology. The aim is to maximize the usage of sustainable cryogenic and hybrid machining technologies in the global manufacturing industry by highlighting their advantages. An overview of in-house developed cryogenic and hybrid machining techniques is presented. Various challenges and future needs related to cryogenic and hybrid-machining techniques are also discussed in the articles. Although remarkable results are obtained with the available literature's delivery methods, there is still no consensus regarding the best cryogenic delivery methods for machining the aforementioned materials. In addition, further hybridization of cryogenic delivery techniques with near dry machining techniques such as minimum quantity lubrication (MQL), electrostatic-MQL (EMQL), and nanofluid based MQL (nMQL) can be beneficial for machinability improvements of difficult-to-machine materials.